PIANO PEDAGOGY IN MUSIC SCHOOL THROUGH THE LENS OF UKRAINIAN PRACTICE AND EUROPEAN APPROACHES - Igor RIABOV; Yaroslav YARMAK; Olena SIKALOVA; Serhii RIABOV; Olena SPOLSKA (Studia Universitatis Babeş-Bolyai. Musica, 2025)
The article examines contemporary approaches to piano pedagogy in the context of the transformation of arts education. It analyzes the interaction between traditional individual teaching methods and new trends, including group teaching, the introduction of digital technologies, multicultural strategies, and interdisciplinary approaches. It summarizes contemporary scientific discussions on rethinking piano teaching methods and points to the risks of completely abandoning the individual approach. Methodologically, the study is based on a comparative analysis of the official programs of music schools and higher art institutions in Ukraine, Poland, Great Britain, and Austria. Particular attention is paid to issues of repertoire policy, class structure, the role of related disciplines, and the integration of national traditions into the educational process. The conclusions justify the importance of preserving individual teaching as a key form of professional competence development for pianists, complemented by innovative and collective forms of work. The article reveals the potential of contemporary piano education in combining traditions, technological solutions, and cultural diversity.